2015
DOI: 10.1111/chd.12271
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Alcohol Consumption before and during Pregnancy and the Risks of Congenital Heart Defects in Offspring: A Systematic Review and Meta-analysis

Abstract: In summary, this meta-analysis provided no positive association between maternal alcohol consumption and risk of CHDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 46 publications
(75 reference statements)
3
22
0
Order By: Relevance
“…Therefore, it is worthwhile that a meta-analysis by Wen et al [ 19 ] found no association between maternal alcohol consumption during pregnancy and the risk of CHDs. These findings confirmed conclusions of a previous systematic review [ 20 ]. The major cause of acquired heart disease in developed countries is represented by coronary artery abnormalities, that is the main complication of KD.…”
Section: Reviewsupporting
confidence: 92%
“…Therefore, it is worthwhile that a meta-analysis by Wen et al [ 19 ] found no association between maternal alcohol consumption during pregnancy and the risk of CHDs. These findings confirmed conclusions of a previous systematic review [ 20 ]. The major cause of acquired heart disease in developed countries is represented by coronary artery abnormalities, that is the main complication of KD.…”
Section: Reviewsupporting
confidence: 92%
“…Congenital heart defects (CHDs) are groups of congenital cardiovascular disorders or diseases that affect about 1% of live births worldwide [1][2][3]; also, it is the leading cause of infant deaths [4]. Based on the data from American Heart Association, there are over 20 common types of CHDs that can be observed in clinic, including but not limited to atrial septal defect (ASD), tetralogy of Fallot (TOF), and conotruncal heart defect (CTD) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Fetal echocardiography in these cases is only indicated if the results of a detailed fetal ultrasound examination ( Current Procedural Terminology code 76811) are abnormal . These conditions include: Gestational diabetes diagnosed after the second trimester Warfarin exposure Alcohol exposure Echogenic intracardiac focus Maternal fever or viral infection with seroconversion only Isolated CHD in a relative further removed from second degree to the fetus …”
Section: Indicationsmentioning
confidence: 99%